Reading poetry based on video modeling techniques of poetry performance records - Aenun Rahmawati (LADU: Journal of Languages and Education, 2023)
Background:  Reading poetry is an effort to convey the poet's message to his listeners. Purpose: This study aims to analyze the process of learning to read poetry and improve results. Design and methods: This experiment analyzes the improvement of the learning process, including the stages of attention, retention, reproduction, and motivation, as well as the improvement of student learning outcomes when reading poetry in terms of intonation, pronunciation, volume, gestures, and expressions. This research was conducted on Literary Club extracurricular students at SDIT ALIF. The method used in this study is a quantitative experimental method using the video modeling technique of recording a poetry performance by Helvy Tiana Rosa. Data analysis techniques in this study were in the form of videos during which students read poetry, observation sheets, field notes, and student test results in the form of performance tests. In this design, two groups are randomly selected and then given a pretest to find out the difference in the initial state between the experimental group and the control group. Each group that was randomly selected was the same for both the control group and the experimental group, namely 10 people Results: experimental class pretest data with an average of 14.10 while the control class obtained an average of 19.60. From the results of the posttest, it was obtained that the average posttest score of the experimental class was 17.50 and that of the control class was 26.30. Thus, it can be said that the skills of students have increased. However, based on the assessment with this technique, there is an insignificant increase in effect